Опыт реализации управляющих систем безопасности и нормальной эксплуатации энергоблоков АЭС - Елисеев, В.В.; Пивоваров, Г.Ю.; Герасименко, К.Е. (Ядерна та радіаційна безпека, 2016)
Приведены сведения об опыте создания программно-технических комплексов (ПТК) управляющих систем безопасности технологических (УСБТ) и управляющих систем нормальной эксплуатации (УСНЭ) энергоблоков АЭС, внедренных на Запорожской АЭС, проектных решениях и базовых компонентах ПТК УСБТ и ПТК УСНЭ. Наведено відомості про досвід створення програмно-технічних комплексів (ПТК) керуючих систем безпеки технологічних (КСБТ) і керуючих систем нормальної експлуатації (КСНЕ) енергоблоків АЕС, впроваджених на Запорізькій АЕС, проектні рішення та базові компоненти ПТК КСБТ і ПТК КСНЕ. The paper deals with instrumentation and control (I&C) of safety control systems (ESFAS) and normal operation control systems (NOCS) for NPP units. The research contains: general information on I&C of ESFAS and I&C of NOCS; description of design solutions for ESFAS, NOCS and principles of their implementation in I&C versions, description of basic components for design of I&C of ESFAS and I&C of NOCS. Distinctive features of ESFAS and NOCS I&Cs are the following: possibility to design systems with different number of channels in accordance with the design requirements; higher reliability due to redundant structures, including redundancy of analog-digital units and control drive units; minimization of cabling due to optical interface of data transmission using digital devices for remote control, indication and alarm in MCR (ECR); possibility of single redundant channel maintenance of I&Cs without losing operability; continuous monitoring of equipment of I&Cs, including diagnosing of input discrete signal channels and detection of hidden faults “on demand”.